Analysis of Stock Portfolio Performance Using The Jensen Method: Case Study of the LQ45 Index on the Indonesian Stock Exchange for the Period 2019-2022 - Musa, Chalid Imran; Anwar (PT. Maju Malaqbi Makkarana, 2023)
Measuring portfolio performance cannot only be seen from the returns, but also must pay attention to the risks that investors will bear. Measuring the performance of a stock portfolio can be facilitated by using a proxy, namely LQ 45 shares, which are liquid stocks with high market capitalization, have high trading frequency, have good growth prospects and financial conditions, are not volatile and have been objectively selected by the IDX and are stocks. which is safe to own because the fundamental performance of these stocks is good, so that from a risk perspective the LQ 45 stock group has the lowest risk compared to other stocks. The research objective was to determine portfolio performance assessment using the Jensen method, a case study of the LQ45 index on the Indonesian stock exchange for the 2019-2022 period. The population in this study is LQ45 index shares on the Indonesian stock exchange for the 2019-2022 period based on a purposive sampling technique. Data collection is documentation and literature study. The data analysis that will be used in this study is by using the Microsoft Excel 2010 application program to form an optimal portfolio using the Single index model and to assess the performance of a stock portfolio using the Jensen index method. the results of portfolio performance analysis of Jensen's Alpha LQ45 index optimal stocks and obtaining an average RVOR value of 0.0207 or 2.07%.